Assessment of the oil scoop capture efficiency in high speed rotors - Paleo Cageao, Paloma; Simmons, Kathy; Prabhakar, Arun; Chandra, Budi (American Society of Mechanical Engineers, 2017)
Experimental research was conducted into a scooped rotor system that captures oil from a stationary jet and directs it through passages within the shaft to another axial location. Such a system has benefits for delivering oil via under-race feed to aeroengine bearings where direct access is limited. Oil capture efficiency was calculated for three jet configurations, a range of geometric variations relative to a baseline and a range of operating conditions. Flow visualization techniques yielded high-speed imaging in the vicinity of the scoop leading edge.